(untitled) (International journal of artificial intelligence, 2026)
Phytonyms play an important role in creating a human image in speech. After all, human life is inextricably linked with flora. This is the first reason why linguists pay special attention to the plant world, and secondly, linguistic units related to plants occupy one of the main places in the world-linguistic landscape of the people. The article reveals the semantic and conceptual features of phytomorphic units in the Turkish language through examples. The use of phytonyms in the language for artistic depiction, their importance in the creation of artistic works, serves to enrich the phytonyms of the Turkish language. Attention is paid to the vocabulary of the language in reflecting the human image through the names of fruits and plants, revealing their characteristics. The article shows that phytonyms serve for artistic imagery, their importance in creating artistic works (fruit, pomegranate, flower, hyacinth, hyacinth, cypress, orange, violet, daffodil, tulip, shamrock, wheat, barley), and serve as an important lexical tool in creating poetic works such as simile, allegory, and diagnosis.